Fluorescence study of natural anthraquinones and chemical constituents of Boesenbergia stenophylla / Nabila Elyana Adnan - Nabila Elyana , Adnan (2018)
Anthraquinones have significant economic values as dyes and pigments and attracted many interests in advanced studies focusing on optical spectroscopy and photochemistry properties. However, these studies are based on unnatural anthraquinones obtained synthetically. The present dissertation work focused on the fluorescence study of natural anthraquinones isolated from Morinda citrifolia. Ten known anthraquinones obtained from the roots of M. citrifolia have been subjected to the fluorescence study. The effects of substituent groups and intramolecular hydrogen bonding on the fluorescence properties were investigated. The present dissertation work also focused on the phytochemical studies of Boesenbergia stenophylla. B. stenophylla from the family of Zingiberacea, is a perennial rhizomatous herb that can be found in the highland areas of Sarawak, Malaysia. In the present study, two new and two known compounds were isolated from B. stenophylla. All the compounds were isolated and characterized using extensive chromatographic and spectroscopic methods. Several of these compounds were selected for antioxidant assay for their ferric reducing antioxidant power (FRAP).